INTERACTION AMONG ZINC, GLUCOSE, AND INSULIN IN NORMAL INDIVIDUALS DURING GLUCOSE AND TOLBUTAMIDE PERFUSION - Neto, J. B.; Vieira, JGH; Shuhama, T.; Russo, EMK; Piesco, R. V.; Curi, P. R. (Humana Press Inc, 1991)
Reports in the literature have shown that acute or chronic zinc administration may cause hyperglycemia, with a fall in serum or insular insulin occurring in experimental animals. on the other hand, under conditions of both acute and chronic hyperglycemia, an increase, a decrease, or a normal level of blood zinc has been observed in studies conducted on humans. Thus, the objective of the investigation described here was to determine the relationship existing among zinc, glucose, and insulin under acute conditions. Thirty-six subjects of both sexes (mean age, 23 yr) were tested at 7:00 A.M. after a 12-h fast. Two antecubital veins of both forearms were punctured and maintained with physiological saline. Three experiments were performed in which zinc was administered orally, and hypertonic glucose and tolbutamid were administered intravenously. Blood samples were then collected over a period ranging from 93 to 240 min after the basal times of - 30 and 0 min. Hyperzincemia did not cause changes in plasma glucose or insulin either in the absence of or during perfusion of glucose. Hyperglycemia, hypoglycemia, and hyperinsulinemia did not modify serum zinc levels. These results demonstrate that acute zinc administration did not change carbohydrate metabolism and that sudden variations in glucose and insulin levels did not modify the serum profile of zinc.